2004
DOI: 10.1128/mcb.24.7.2649-2661.2004
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box M1B Transcriptional Activity Requires Binding of Cdk-Cyclin Complexes for Phosphorylation-Dependent Recruitment of p300/CBP Coactivators

Abstract: Previous liver regeneration studies demonstrated that the mouse forkhead box M1B (FoxM1B) transcription factor regulates hepatocyte proliferation through expression of cell cycle genes that stimulate cyclin-dependent kinase 2 (Cdk2) and Cdk1 activity. In this study, we demonstrated that disruption of the FoxM1B Cdk1/2 phosphorylation site at Thr residue 596 significantly reduced both FoxM1B transcriptional activity and Cdk phosphorylation of the FoxM1B T596A mutant protein in vivo. Retention of this FoxM1B 596… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
280
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(295 citation statements)
references
References 71 publications
(133 reference statements)
11
280
1
Order By: Relevance
“…[87][88][89] The transcriptional activity of Foxm1b appears to require docking with cdk2-cyclin E/A (S Phase) or Cdk1-Cyclin B (G 2 Phase) complexes and recruitment of the p300 coactivator. 90 In a recent study, Kalinchenko et al have validated the importance of Foxm1b for the development of hepatocellular carcinoma in an experimental carcinogenesis model. 91 Foxm1b -/-hepatocytes were found to be resistant to the development of HCC following the diethylnitrosamine/phenobarbital tumor induction protocol.…”
Section: Factors Implicated In G 2 /M Mitotic Checkpoint Regulationmentioning
confidence: 97%
“…[87][88][89] The transcriptional activity of Foxm1b appears to require docking with cdk2-cyclin E/A (S Phase) or Cdk1-Cyclin B (G 2 Phase) complexes and recruitment of the p300 coactivator. 90 In a recent study, Kalinchenko et al have validated the importance of Foxm1b for the development of hepatocellular carcinoma in an experimental carcinogenesis model. 91 Foxm1b -/-hepatocytes were found to be resistant to the development of HCC following the diethylnitrosamine/phenobarbital tumor induction protocol.…”
Section: Factors Implicated In G 2 /M Mitotic Checkpoint Regulationmentioning
confidence: 97%
“…In our study, cell cycle analysis revealed that inhibition of FoxM1 by dexamethasone and siomycin A decreased the proliferation of T-ALL cells significantly through induction of G1 phase arrest. Recent studies have shown that FoxM1 phosphorylation starts at early G1 with cyclin-CDK complexes and continues throughout the G2 phase and mitosis [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…FoxM1 has been shown to activate the oncogenic pathways that are important in carcinogenesis such as mitogen activated protein kinase (MAPK), extracellular signal-regulated kinase (ERK), phosphatdyl inositol 3-kinase (PI3k)/Akt), nuclear factor kappa-B and sonic hedgehog (SHH) [33][34][35][36][37]. Moreover, FoxM1 has been shown to decrease the gene expression levels of the tumor suppressor genes and also the genes involved in cellular senescence like p53 and p21 cip1 [20,38].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of E2F-1 to stimulate transcription appears to be subjected to multiple regulations including co-activation by CBP/p300 and reversal of Rb-mediated repression through Rb phosphorylation [55]. At a molecular level, the Cdk-stimulated interaction of CBP/p300 with E2F-1 may be involved in irreversibly committing cells to cell-cycle progression [56]. Interestingly, although E2F-1 has been shown to be acetylated in vitro by both p/CAF and CBP/p300 at the same lysine residues, a specific role for p/CAF in acetylation-induced stabilisation of E2F-1 in response to DNA damage was recently reported [57].…”
Section: Potential Therapeutic Approachesmentioning
confidence: 99%